Monetary Policy and the Financing of Firms - Fiorella De Fiore; Pedro Teles; Oreste Tristani (European Central Bank (ECB), 2009)
How should monetary policy respond to changes in financial conditions? In this paper we consider a simple model where firms are subject to idiosyncratic shocks which may force them to default on their debt. Firms' assets and liabilities are denominated in nominal terms and predetermined when shocks occur. Monetary policy can therefore affect the real value of funds used to finance production. Furthermore, policy affects the loan and deposit rates. In our model, allowing for short-term inflation volatility in response to exogenous shocks can be optimal; the optimal response to adverse financial shocks is to lower interest rates, if not at the zero bound, and to engineer a short period of controlled inflation; the Taylor rule may implement allocations that have opposite cyclical properties to the optimal ones.
Keywords: E20; E44; E52; 330; bankruptcy costs; debt deflation; financial stability; optimal monetary policy; price level volatility; stabilization policy; Geldpolitik; Konjunktur; Unternehmensfinanzierung; Schock; Insolvenz; Zinspolitik; Inflation; Taylor-Regel; Theorie